A national descriptive epidemiologic analysis on congenital pulmonary airway malformation in China, 2010–2019. Issue 3 (11th January 2022) - Xu, Wenli; Gao, Yuyang; Li, Wenyan; Chen, Zhiyu; Li, Qi; Li, Ruike; Liu, Hanmin; Dai, Li
Abstract: Objective: To depict the epidemiological features of congenital pulmonary airway malformation (CPAM) in Chinese population. Methods: Using 2010–2019 data from the Chinese Birth Defects Monitoring Network, we calculated the prevalence rates (PR) and 95% confidence intervals of isolated and nonisolated CPAM according to birth year, infant sex, maternal age and residence area, and examined the secular trends by using Poisson regression models. The perinatal outcomes of affected infants and associated malformations with CPAM were also analyzed. Results: During this period, a total of 2451 CPAMs were identified among 20, 183, 999 births, yielding a PR of 1.21, 0.95, and 0.27 per 10, 000 live and still births for the overall, isolated and nonisolated CPAM, respectively. Significant upward trends in CPAM PR were observed. The PR varied significantly by infant sex (male vs. female, 1.28/10, 000 vs. 1.10/10, 000), residence area (urban vs. rural, 1.49/10, 000 vs. 0.88/10, 000), and by maternal age (<20 years, 0.94/10, 000; 20–24 years, 1.04/10, 000; 25–29 years, 1.32/10, 000; 30–34 years, 1.28/10, 000; ≥35 years, 1.05/10, 000). Compared with isolated CPAM, much more live births with nonisolated CPAM died in the early neonatal period (5.0% vs. 1.0%). The additional malformations with nonisolated CPAM occurred most frequently in the circulatory system. Conclusions: The PR of CPAM in this study are comparable to those reported in non‐Chinese populations. The increasing trend in prevalence and poor perinatal outcomes of the affected infants indicate an urgent need to strengthen the clinical and public health interventions of CPAM.